Mapeamento participativo em um contexto de conflito territorial : a experiência com a população indígena da Chapada do Á, Anchieta-ES, Brasil - Roquette, Maria Elisa Tosi (2015)
The research investigates the participatory mapping experience with a community selfidentified indigenous, Tupiniquim ethnicity. The community in question is Chapada do Á, municipality of Anchieta (ES), which is in a context of territorial disputes arising from the attempts to implement steel companies in the region. To contribute with an instrument that could expand the possibilities of community mobilization for their struggles we developed with them a participatory mapping experience, which also served as the basis to discuss methodological issues. We used oral histories to understand the context in which the community is inserted as well as the process of constitution of territorial identity. From the literature review we systematize discussions about fundamental geography concepts required for analysis and about participatory mapping. We conclude that a major obstacle to the development of participatory mapping practice is time, as it influences other key areas to participatory activities such as confidence-building, stakeholder participation and the unveiling of the power relations and the training of participants for the use of tools, mainly GIS. In addition, the role of facilitation also strongly influences the points mentioned above, in particular the participation of different groups within a community. Greater attention should be paid to the initial stages of participatory mapping and we highlight here a greater need to reflect the legend, an exercise that should take place throughout the process. On the other hand, the participatory mapping practice makes room for the exchange of traditional knowledge and turn into an arena for discussions of the territory. Finally, we understand that participatory mapping when making the use of traditional cartography’s tools can affect the spatial understanding of traditional communities’ participants, however, also reinsert them in ‘empty’ state maps.